Suspended sediment transport dynamics in rivers: Multi-scale drivers of temporal variation - Vercruysse, Kim; Grabowski, Robert C.; Rickson, R. Jane (Elsevier, 2017)
Suspended sediment is a natural part of river systems and plays an essential role in structuring the landscape, creating ecological habitats and transporting nutrients. It is also a common management problem, where alterations to sediment quantity and quality negatively impact ecological communities, increase flood hazard and shorten the lifespan of infrastructure. To address these challenges and develop appropriate sustainable management strategies, we need a thorough understanding of sediment sources, pathways and transport dynamics and the drivers that underlie spatial and temporal variability in suspended sediment transport in rivers. However, research to date has not sufficiently addressed the temporal complexity of sediment transport processes, which is limiting our ability to disentangle the hydro-meteorological, catchment, channel and anthropogenic drivers of suspended sediment transport in rivers. This review critically evaluates previously published work on suspended sediment dynamics to demonstrate how the interpretation of sediment sources and pathways is influenced by the temporal scale and methodology of the study. To do this, the review (i) summarizes the main drivers of temporal variation in suspended sediment transport in rivers; (ii) critically reviews the common empirical approaches used to analyze and quantify sediment sources and loads, and their capacity to account for temporal variations; (iii) applies these findings to recent case studies to illustrate how method and timescale affect the interpretation of suspended sediment transport dynamics; and finally (iv) synthesizes the findings of the review into a set of guidelines for a multi-timescale approach to sediment regime characterization. By recognizing a priori that study design and temporal scale have an impact on the interpretation of SS dynamics and employing methods that address these issues, future research will be better able to identify the drivers of suspended sediment transport in rivers, improve sediment transport modelling, and propose effective, sustainable solutions to sediment management problems.
Keywords: Suspended sediment; Regime; Load; Catchment; Timescale; Drivers